Analysis of Factors Related to the Use of Iud Contraceptives in the Working Area - Ikke Kristiya; Siti Nurhajjah; Hudila Rifa Karmia (Journal La Medihealtico, 2025)
The growth of the world's population is increasing day by day, the increase in the number of people also has an impact on the maternal mortality rate (AKI), The factor that causes the increase in population is the lack of people in the use of contraception, especially in the use of long-term contraception, one of which is IUD. The purpose of this study is to find out "Factors Related to the Use of IUD Contraceptives in the Working Area of the Andalas Padang Health Center This type of research is analytical with a Cross Sectional design, which will be carried out from June 2024 to January 2025. A sample of 68 PUS people using IUD contraceptives was taken using propotional random sampling. Data collection was conducted using questionnaires and analyzed using Chi Square and Logistic Regression tests. The results of the study found that the level of knowledge was high (69.1%), positive attitude (79.4%), support for husbands who did not support (60.3%), and support for health workers (75.0%). Based on multivariate results, it was found that the most dominant factor related to the use of IUD contraceptives was the husband's support with the highest OR value of 4,398. The conclusion of this study found that there was a relationship between the level of knowledge, attitude, husband support and health worker support. The most dominant factor is the husband's support. It is hoped that there will be cross-sectoral cooperation and education in the role of husbands to increase the use of IUD contraceptives in PUS.